Research and policy priorities to address drought and irrigation water resource risks in temperate agriculture - Holman, Ian P.; Knox, Jerry W. (Cambridge University Press (CUP), 2023)
Droughts are a major global natural hazard, creating negative environmental and socio-economic impacts across a broad spectrum of sectors. However, agriculture is often the first sector to be impacted due to prolonged rainfall shortages reducing available soil moisture reserves with negative consequences for both rainfed and irrigated food crop production and for livestock. In the UK, recent droughts in 2018 and 2022 have highlighted the vulnerability of the agricultural and horticultural sectors since most production is rainfed and entirely dependent on the capricious nature of summer rainfall. Surprisingly, despite recognition of the agronomic and economic risks, there remains a paucity of evidence on the multi-scalar impacts of drought, including the impacts on crop yields and quality, the financial implications for farming and the consequences for fresh produce supply chains. Drawing on published grey and science literature, this review provides a comprehensive synthesis of drought impacts on U.K. agriculture, including characterisation of the sensitivity of the main sub-sectors to different types of drought, a critique of the short-term coping responses and longer-term strategies and identification of the main knowledge gaps which need to be addressed through a concerted effort of research and development to inform future policies focussing on climate change risk assessment for agriculture. Although the review focuses predominantly on U.K. evidence, the insights and findings are relevant to understanding drought impacts and risk management strategies in other temperate and humid regions where agriculture is a fundamentally important component of the economy.
Keywords: adaptation; farming; food systems; irrigation; resilience